"He is clean he is straight he is incorruptible he is tough he is efficient - " [Bob Hawke, Neville Wran, Australian Labor Party] - Pryor, Geoff, 1944- (1985)
Labor Prime Minister Bob Hawke addresses the NSW State Labor Conference and launches a campaign to restore the credibility of Premier Neville Wran and his State Labor Government which is languishing in the polls amid a welter of accusations of corruption and the infiltration of shady types with criminal associations.--Information supplied by Geoff Pryor.
Title devised by cataloguer.
Published in the Canberra Times 11 June 1985.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Wran, Neville, -- 1926-2014 -- Caricatures and cartoons; Hawke, Bob, -- 1929-2019 -- Caricatures and cartoons; Australian Labor Party -- Caricatures and cartoons; Politicians -- Australia -- Caricatures and cartoons; Politicians -- New South Wales -- Caricatures and cartoons; Australia -- Politics and government -- 1976-1990 -- Caricatures and cartoons; Federal politicians; State and Territory politicians